Skip to main content

Generalized Fibonacci sequences in groupoids

Abstract

In this paper, we introduce the notion of generalized Fibonacci sequences over a groupoid and discuss it in particular for the case where the groupoid contains idempotents and pre-idempotents. Using the notion of Smarandache-type P-algebra, we obtain several relations on groupoids which are derived from generalized Fibonacci sequences.

MSC:11B39, 20N02, 06F35.

1 Introduction

Fibonacci-numbers have been studied in many different forms for centuries and the literature on the subject is consequently incredibly vast. Surveys and connections of the type just mentioned are provided in [1] and [2] for a very minimal set of examples of such texts, while in [3] an application (observation) concerns itself with the theory of a particular class of means which has apparently not been studied in the fashion done there by two of the authors of the present paper. Han et al. [4] studied a Fibonacci norm of positive integers, and they presented several conjectures and observations.

Given the usual Fibonacci-sequences [1, 2] and other sequences of this type, one is naturally interested in considering what may happen in more general circumstances. Thus, one may consider what happens if one replaces the (positive) integers by the modulo integer n or what happens in even more general circumstances. The most general circumstance we will deal with in this paper is the situation where (X,) is actually a groupoid, i.e., the product operation is a binary operation, where we assume no restrictions a priori. Han et al. [5] considered several properties of Fibonacci sequences in arbitrary groupoids.

The notion of BCK-algebras was introduced by Iséki and Imai in 1966. This notion originated from both set theory and classical and non-classical propositional calculi. The operation in BCK-algebras is an analogue of the set-theoretical difference. Nowadays, BCK-algebras have been studied by many authors and they have been applied to many branches of mathematics such as group theory, functional analysis, probability theory, topology and fuzzy theory [68] and so on. We refer to [9, 10] for further information on BCK/BCI-algebras.

Let (X,) be a groupoid (or an algebra). Then (X,) is a Smarandache-type P-algebra if it contains a subalgebra (Y,), where Y is non-trivial, i.e., |Y|2, or Y contains at least two distinct elements, and (Y,) is itself of type P. Thus, we have Smarandache-type semigroups (the type P-algebra is a semigroup), Smarandache-type groups (the type P-algebra is a group), Smarandache-type Abelian groups (the type P-algebra is an Abelian group). Smarandache semigroup in the sense of Kandasamy is in fact a Smarandache-type group (see [11]). Smarandache-type groups are of course a larger class than Kandasamy’s Smarandache semigroups since they may include non-associative algebras as well.

In this paper, we introduce the notion of generalized Fibonacci sequences over a groupoid and discuss it in particular for the case where the groupoid contains idempotents and pre-idempotents. Using the notion of Smarandache-type P-algebra, we obtain several relations on groupoids which are derived from generalized Fibonacci sequences.

2 Preliminaries

Given a sequence φ 0 , φ 1 ,, φ n , of elements of X, it is a left--Fibonacci sequence if φ n + 2 = φ n + 1 φ n for n0, and a right--Fibonacci sequence if φ n + 2 = φ n φ n + 1 for n0. Unless (X,) is commutative, i.e., xy=yx for all x,yX, there is no reason to assume that left--Fibonacci sequences are right--Fibonacci sequences and conversely. We will begin with a collection of examples to note what, if anything, can be concluded about such sequences.

Example 2.1 Let (X,) be a left-zero-semigroup, i.e., xy:=x for any x,yX. Then φ 2 = φ 1 φ 0 = φ 1 , φ 3 = φ 2 φ 1 = φ 2 = φ 1 , φ 4 = φ 3 φ 2 = φ 3 = φ 1 , … for any φ 0 , φ 1 X. It follows that φ n L = φ 0 , φ 1 , φ 1 ,. Similarly, φ 2 = φ 0 φ 1 = φ 0 , φ 3 = φ 1 φ 2 = φ 1 , φ 4 = φ 2 φ 3 = φ 2 = φ 0 , … for any φ 0 , φ 1 X. It follows that φ n R = φ 0 , φ 1 , φ 0 , φ 1 , φ 0 , φ 1 ,. In particular, if we let φ 0 :=0, φ 1 :=1, then φ n L =0,1,1,1,1, and φ n R =0,1,0,1,0,1,.

Theorem 2.2 Let φ n L and φ n R be the left--Fibonacci and the right--Fibonacci sequences generated by φ 0 and φ 1 . Then φ n L = φ n R if and only if φ n ( φ n 1 φ n )=( φ n φ n 1 ) φ n for any n1.

A d-algebra [12](X,,0) is an algebra satisfying the following axioms: (D1) xx=0 for all xX; (D2) 0x=0 for all xX; (D3) xy=yx=0 if and only if x=y.

A BCK-algebra [13] is a d-algebra X satisfying the following additional axioms:

(D4) ((xy)(xz))(zy)=0,

(D5) (x(xy))y=0 for all x,y,zX.

Given algebra types (X,) (type- P 1 ) and (X,) (type- P 2 ), we will consider them to be Smarandache disjoint [11] if the following two conditions hold:

  1. (i)

    If (X,) is a type- P 1 -algebra with |X|>1, then it cannot be a Smarandache-type- P 2 -algebra (X,);

  2. (ii)

    If (X,) is a type- P 2 -algebra with |X|>1, then it cannot be a Smarandache-type- P 1 -algebra (X,).

This condition does not exclude the existence of algebras (X,) which are both Smarandache-type- P 1 -algebras and Smarandache-type- P 2 -algebras. It is known that semigroups and d-algebras are Smarandache disjoint [11].

It is known that if (X,,0) is a d-algebra, then it cannot be a Smarandache-type semigroup, and if (X,) is a semigroup, then it cannot be a Smarandache-type d-algebra [11].

3 Generalized Fibonacci sequences over (X,)

Let Z 2 [[X]] denote the power-series ring over the field Z 2 ={0,1}. Given p(x)= p 0 + p 1 x+ p 2 x 2 + Z 2 [[X]], we associate a sequence p ( x ) ={ λ 0 , λ 1 , λ 2 ,}, where λ i =L if p i =0 and λ i =R if p i =1, which gives some information to construct a generalized Fibonacci sequence in a groupoid (X,).

Given a groupoid (X,) and a power-series p(x) Z 2 [[X]], if a,bX, we construct a sequence as follows:

[ a , b ] p ( x ) :={a,b, u 0 , u 1 , u 2 ,, u k ,},

where

u 0 : = { a b if  λ 0 = R , b a if  λ 0 = L , u 1 : = { b u 0 if  λ 1 = R , u 0 b if  λ 1 = L and u k + 2 : = { u k u k + 1 if  λ k + 2 = R , u k + 1 u k if  λ k + 2 = L .

We call such a sequence [ a , b ] p ( x ) a p(x)-Fibonacci sequence over (X,) or a generalized Fibonacci sequence over (X,).

Example 3.1 Let (X,) be a groupoid and a,bX. If p(x)=1+0x+1 x 2 +1 x 3 +0 x 4 + is a sequence in Z 2 [[X]], then we obtain p ( x ) ={R,L,R,R,L,L,} and its p(x)-Fibonacci sequence [ a , b ] p ( x ) can be denoted as follows: [ a , b ] p ( x ) :={a,b, u 0 , u 1 , u 2 ,}, where u 0 =ab, u 1 = u 0 b=(ab)b, u 2 = u 0 u 1 =(ab)[(ab)b], u 3 = u 1 u 2 =[(ab)b]{(ab)[(ab)b]}, u 4 = u 3 u 2 =[[(ab)b]{(ab)[(ab)b]}][(ab)[(ab)b]], … .

Example 3.2 (a) Let (X,) be a right-zero semigroup and let p 0 (x):=0+0 x 1 +0 x 2 +0 x 3 + . Then p 0 ( x ) ={L,L,L,} and hence [ a , b ] p 0 ( x ) ={a,b,ba=a,(ba)b=b,[(ba)b](ba)=a,}={a,b,a,b,a,b,} for any a,bX.

  1. (b)

    Let (X,) be a left-zero semigroup and let p 1 (x):=1+x+ x 2 + x 3 + . Then p 1 ( x ) ={R,R,R,} and hence [ a , b ] p 1 ( x ) ={a,b,a,b,a,b,} for any a,bX.

Example 3.3 If we let S(x):=x+ x 3 + x 5 + and C(x):=1+ x 2 + x 4 + x 6 + , then S(x)+C(x)= p 1 (x) and S(x)=xC(x). It follows that S ( x ) ={L,R,L,R,} and C ( x ) ={R,L,R,L,R,}. Let (X,) be a groupoid and let a,bX. Then [ a , b ] S ( x ) ={a,b,ba,b(ba),(b(ba))(ba),} and [ a , b ] C ( x ) ={a,b,ab,(ab)b,(ab)((ab)b),}.

Let p(x) Z 2 [[X]]. A groupoid (X,) is said to be power-associative if, for any a,bX, there exists kZ such that the generalized Fibonacci sequence [ a , b ] p ( x ) has u k 2 = u k 1 =u for some uX.

Proposition 3.4 Let p(x) Z 2 [[X]]. Let (X,) be a groupoid having an identity e, i.e., xe=x=ex for all xX. Then (X,) is power-associative if, for any a,bX, [ a , b ] p ( x ) contains e.

Proof If [ a , b ] p ( x ) contains e, then there exists an uX such that [ a , b ] p ( x ) has ,u,e, . Since [ a , b ] p ( x ) is a generalized Fibonacci sequence, it contains ,u,e,ue=eu=u,eu=ue=u, , proving that (X,) is power-associative. □

Let (X,) be a semigroup and let xX. We denote x 2 :=xx, and x n + 1 := x n x=x x n , where n is a natural number.

Theorem 3.5 Let p(x) Z 2 [[X]]. Let (X,) be a semigroup and let a,bX. If it is power-associative, then [ a , b ] p ( x ) contains a subsequence { u k } such that u k + n = u F n + 3 for some uX, where F n is the usual Fibonacci number.

Proof Given a,bX, since (X,) is power-associative, [ a , b ] p ( x ) contains an element u such that u k 2 = u k 1 =u. It follows that either u k = u k 1 u k 2 =uu= u 2 or u k = u k 2 u k 1 =uu= u 2 . This shows that either u k + 1 = u k u k 1 = u 2 u= u 3 or u k + 1 = u k 1 u k =u u 2 = u 3 . In this fashion, we have u k + 2 = u 5 , u k + 3 = u 8 = u F 6 ,, u k + n = u F n + 3 . □

Let (X,) be a groupoid having the following conditions:

  1. (A)

    x(yx)=x,

  2. (B)

    (xy)y=xy for all x,yX.

Given p 1 (x)= n = 0 x n , for any a,bX, a generalized Fibonacci sequence [ a , b ] p 1 ( x ) has the following periodic sequence:

[ a , b ] p 1 ( x ) = { a , b , a b , b ( a b ) , ( a b ) ( b ( a b ) ) , } = { a , b , a b , b , a b , b , a b , } .

We call this kind of a sequence periodic.

A BCK-algebra (X,,0) is said to be implicative [13] if x=x(yx) for all x,yX.

Proposition 3.6 Let (X,,0) be an implicative BCK-algebra and let a,bX. Then the generalized Fibonacci sequence [ a , b ] p 1 ( x ) is periodic.

Proof Every implicative BCK-algebra satisfies the conditions (A) and (B). □

Proposition 3.7 Let (X,,0) be a BCK-algebra and let a,bX. Then the generalized Fibonacci sequence [ a , b ] p 0 ( x ) is of the form {a,b,ba,0,0,0,}.

Proof If (X,,0) is a BCK-algebra, then (xy)x=(xx)y=0y=0 for all x,yX. It follows that [ a , b ] p 0 ( x ) ={a,b,ba,(ba)b=0,0(ba)=0,00=0,0,0,}. □

4 Idempotents and pre-idempotents

A groupoid (X,) is said to have an exchange rule if (xy)z=(xz)y for all x,y,zX.

Proposition 4.1 Let a groupoid (X,) have an exchange rule and let b be an idempotent in X. Then [ a , b ] p 0 ( x ) ={a,b,ba, ( b a ) 2 , ( b a ) 3 , ( b a ) 4 ,} for all aX.

Proof Given a,bX, since (X,) has an exchange rule, (ba)b=(bb)a. It follows from b is an idempotent that bb=b. This proves that [ a , b ] p 0 ( x ) ={a,b,ba,(ba)b=(bb)a=ba,(ba)(ba)= ( b a ) 2 , ( b a ) 3 ,}. □

Corollary 4.2 Let a groupoid (X,) have an exchange rule and let b and ba be idempotents in X. Then [ a , b ] p 0 ( x ) ={a,b,ba,ba,ba,}.

Proof Straightforward. □

A groupoid (X,) is said to have an opposite exchange rule if x(yz)=y(xz) for all x,y,zX.

Proposition 4.3 Let a groupoid (X,) have an opposite exchange rule and let b be an idempotent in X. Then [ a , b ] p 1 ( x ) ={a,b,ab, ( a b ) 2 , ( a b ) 3 , ( a b ) 4 ,} for all aX.

Proof Given a,bX, since (X,) has an opposite exchange rule and b is an idempotent in X, b(ab)=a(bb)=ab and (ab)[b(ab)]=(ab)(ab)= ( a b ) 2 . This proves that [ a , b ] p 1 ( x ) ={a,b,ab, ( a b ) 2 , ( a b ) 3 , ( a b ) 4 ,}. □

Proposition 4.4 Let (X,) be a groupoid having the condition (B). If b(ba) is an idempotent in X for some a,bX, then [ a , b ] S ( x ) ={a,b,ba,b(ba),b(ba),}.

Proof Given a,bX, since (X,) has the condition (B), we have (b(ba))(ba)=b(ba) and [b(ba)][(b(ba))(ba)]=(b(ba))(b(ba)). Since b(ba) is an idempotent in X, it follows that [ a , b ] S ( x ) ={a,b,ba,b(ba),b(ba),}. □

Proposition 4.5 Let (X,) be a groupoid having the condition (B). If ab is an idempotent in X for some a,bX, then [ a , b ] C ( x ) ={a,b,ab,ab,ab,}.

Proof The proof is similar to Proposition 4.4. □

A groupoid (X,) is said to be pre-idempotent if xy is an idempotent in X for any x,yX. Note that if (X,) is an idempotent groupoid, then it is a pre-idempotent groupoid as well. If (X,,f) is a leftoid, i.e., xy:=f(x) for some map f:XX, then f(f(x))=f(x) implies (X,,f) is a pre-idempotent groupoid.

Theorem 4.6 Let (X,) be a groupoid. Let uX such that [ a , b ] p ( x ) ={a,b,u,u,} for any a,bX. Then (X,) is a pre-idempotent groupoid, and

  1. (i)

    if p(x)=0, then (ba)b=ba,

  2. (ii)

    if p(x)=1, then (ab)b=ab,

  3. (iii)

    if p(x)=x, then b(ba)=ba,

  4. (iv)

    if p(x)=1+x, then b(ab)=ab.

Proof (i) If p(x)=0, then [ a , b ] p ( x ) ={a,b,ba,(ba)b,((ba)b)(ba),}. It follows that (ba)b=ba and ba=((ba)b)(ba)=(ba)(ba), proving that (X,) is a pre-idempotent groupoid with (ba)b=ba.

  1. (ii)

    If p(x)=1, then [ a , b ] p ( x ) ={a,b,(ab)b,((ab)b)(ab),}. It follows that (ab)b=ab and ab=((ab)b)(ab)=(ab)(ab), proving that (X,) is a pre-idempotent groupoid with (ab)b=ab.

  2. (iii)

    If p(x)=1x, then [ a , b ] p ( x ) ={a,b,ba,b(ba),(b(ba))(ba),}. It follows that b(ba)=ba and ba=(b(ba))(ba)=(ba)(ba), proving that (X,) is a pre-idempotent groupoid with b(ba)=ba.

  3. (iv)

    If p(x)=1+1x, then [ a , b ] p ( x ) ={a,b,ab,b(ab),(ab)(b(ab)),}. It follows that b(ab)=ab and ab=(ab)(b(ab))=(ab)(ab), proving that (X,) is a pre-idempotent groupoid with b(ab)=ab. □

Remark Not every generalized Fibonacci sequence has such an element u in X as in Theorem 4.6 in the cases of BCK-algebras.

Example 4.7 Let X:={0,1,2,3} be a set with the following table:

Then (X,,0) is a BCK-algebra. If we let p(x):=1+0x, then it is easy to see that [ 1 , 2 ] p ( x ) ={1,2,1,2,0,0,}, [ 2 , 3 ] p ( x ) ={2,3,0,0,}, [ 3 , 2 ] p ( x ) ={3,2,1,1,0,0,}.

A groupoid (X,) is said to be a semi-lattice if it is idempotent, commutative and associative.

Theorem 4.8 If (X,) is a semi-lattice and p(x)= p 0 + p 1 x Z 2 [[x]], then there exists an element uX such that [ a , b ] p ( x ) ={a,b,u,u,} for any a,bX.

Proof If (X,) is a semi-lattice, then it is a pre-idempotent groupoid. Given a,bX, we have (ba)b=(ab)b=a(bb)=ab, b(ba)=(ba)a=ba, b(ab)=(ba)b=(ab)b=a(bb)=ab, (ab)b=a(bb)=ab. If we take u:=ab, then [ a , b ] p ( x ) ={a,b,u,u,} for any a,bX, in any case of Theorem 4.6. □

5 Smarandache disjointness

Proposition 5.1 The class of d-algebras and the class of pre-idempotent groupoids are Smarandache disjoint.

Proof Let (X,,0) be both a d-algebra and a pre-idempotent groupoid. Then ab=(ab)(ab)=0 and ba=(ba)(ba)=0, by pre-idempotence and (D2), for any a,bX. By (D3), it follows that a=b, which proves that |X|=1. □

Proposition 5.2 The class of groups and the class of pre-idempotent groupoids are Smarandache disjoint.

Proof Let (X,,0) be both a group and a pre-idempotent groupoid. Then, for any xX, we have x=xe=(xe)(xe)=xx. It follows that e=x x 1 =(xx) x 1 =x(x x 1 )=xe=x, proving that |X|=1. □

A groupoid (X,) is said to be an L 4 -groupoid if, for all a,bX,

(L1) ((ba)b)(ba)=ba,

(L2) (ba)((ba)b)=(ba)b.

Example 5.3 Let X:=R be the set of all real numbers. Define a map φ:XX by φ(x):=x 1 2 , where x is the ceiling function. Then φ(φ(x))=φ(x) 1 2 =x 1 2 1 2 =φ(x) 1 2 =φ(x). Define a binary operation ‘’ on X by xy:=φ(y) for all x,yX. Then (X,) is an L 4 -groupoid. In fact, for all a,bX, ((ba)b)(ba)=φ(b)φ(a)=φ(φ(a))=φ(a)=ba. Moreover, (ba)((ba)b)=φ(a)φ(b)=φ(φ(b))=φ(b)=(ba)b.

Proposition 5.4 Let (X,) be a groupoid and let p(x) Z 2 [[x]] such that p(x)= x 4 q(x) for some q(x) Z 2 [[x]]. If there exist u,vX such that [ a , b ] p ( x ) ={a,b,u,v,u,v, α 1 , α 2 ,}, where α i Z 2 for any a,bX, then (X,) is an L 4 -groupoid.

Proof Since p(x)= x 4 q(x), we have p ( x ) ={L,L,L,L, α 1 , α 2 ,}, where α i {L,R}. It follows that [ a , b ] p ( x ) ={a,b,ba,(ba)b,((ba)b)(ba),(((ba)b)(ba))((ba)b),}. This shows that u=ba, v=(ba)b, and hence ((ba)b)(ba)=ba and (ba)((ba)b)=(ba)b, proving the proposition. □

Proposition 5.5 Every L 4 -groupoid is pre-idempotent.

Proof Given a,bX, we have (ba)(ba)=((ba)b)(ba)=ba, proving the proposition. □

Proposition 5.6 The class of L 4 -groupoids and the class of groups are Smarandache disjoint.

Proof Let (X,) be both an L 4 -groupoid and a group with identity e. Then ((ba)b)(ba)=ba for all a,bX. Since any group has the cancellation laws, we obtain (ba)b=e. If we apply this to (L2), then we have (ba)e=e. This means that ba=e. It follows that e=ba=((ba)b)(ba)=(eb)e=b, proving that |X|=1. □

Proposition 5.7 The class of L 4 -groupoids and the class of BCK-algebras are Smarandache disjoint.

Proof Let (X,) be both an L 4 -groupoid and a BCK-algebra with a special element 0X. Given a,bX, we have 0=0a=(bb)a=(ba)b=(ba)((ba)b)=(ba)0=ba. Similarly, ab=0. Since X is a BCK-algebra, a=b for all a,bX, proving that X={0}. □

Let p(x) Z 2 [[x]]. A groupoid (X,) is said to be a Fibonacci semi-lattice if for any a,bX, there exists u=u(a,b,p(x)) in X depending on a, b, p(x) such that [ a , b ] p ( x ) ={a,b,u,u,}.

Note that every Fibonacci semi-lattice is a pre-idempotent groupoid satisfying one of the conditions (ba)b=ab, b(ba)=ba, b(ab)=ab, (ab)b=ab separately (and simultaneously).

Proposition 5.8 Let (X,) be a groupoid and let p(x) Z 2 [[x]] such that p(x)= x 3 q(x) for some q(x) Z 2 [[x]] with q 0 =1. Then (X,) is a Fibonacci semi-lattice.

Proof Since p(x)= x 3 q(x), where q(x) Z 2 [[x]] with q 0 =1, we have p ( x ) ={L,L,L,R, α 1 , α 2 ,}, where α i {L,R}. If we let u:=ba, v:=(ba)b, then [ a , b ] p ( x ) ={a,b,ba=u,(ba)b=v,((ba)b)(ba)=vu=u,}. It follows that ba=u=vu=v=(ba)b. Hence [ a , b ] p ( x ) ={a,b,ba,ba,}, proving the proposition. □

A groupoid (X,) is said to be an LRL 2 -groupoid if for all a,bX,

( LRL 2 1) (b(ba))(ba)=ba,

( LRL 2 2) (ba)(b(ba))=b(ba).

Proposition 5.9 Let (X,) be a groupoid and let p(x) Z 2 [[x]] such that p 0 = p 2 = p 3 =0, p 1 =1. Then (X,) is an LRL 2 -groupoid.

Proof Since p(x) Z 2 [[x]] such that p 0 = p 2 = p 3 =0, p 1 =1, we have p ( x ) ={L,R,L,L, α 1 , α 2 ,}, where α i {L,R}. If we let u:=ba, v:=b(ba), then [ a , b ] p ( x ) ={a,b,ba=u,b(ba)=v,(b(ba))(ba)=u,[(b(ba))(ba)][b(ba)],}. It follows that (b(ba))(ba)=ba and (ba)(b(ba))=b(ba), proving the proposition. □

Proposition 5.10 The class of LRL 2 -groupoids and the class of groups are Smarandache disjoint.

Proof Let (X,) be both an LRL 2 -groupoid and a group with a special element eX. Given a,bX, we have (b(ba))(ba)=ba. Since every group has cancellation laws, we obtain b(ba)=e. It follows that ba=(ba)e=(ba)(b(ba))=b(ba)=e, and hence e=b(ba)=be=b. This proves that |X|=1, proving the proposition. □

A groupoid (X,) is said to be an R 4 -groupoid if for all a,bX,

( R 4 1) (ab)(b(ab))=ab,

( R 4 2) (b(ab))(ab)=b(ab).

Proposition 5.11 Let (X,) be a groupoid and let p(x) Z 2 [[x]] such that p 0 = p 1 = p 2 = p 3 =1. Then (X,) is an R 4 -groupoid.

Proof Since p(x) Z 2 [[x]] such that p 0 = p 1 = p 2 = p 3 =1, we have p ( x ) ={R,R,R,R, α 1 , α 2 ,}, where α i {L,R}. If we let u:=ab, v:=b(ab), then [ a , b ] p ( x ) ={a,b,ab=u,b(ab)=v,(ab)(b(ab))=u,[b(ab)][(ab)(b(ab))],}. It follows that ab=u=uv=(ab)(b(ab)) and b(ab)=v=vu=(b(ab))(ab), proving the proposition. □

Theorem 5.12 The class of R 4 -groupoids and the class of groups are Smarandache disjoint.

Proof Let (X,) be both an R 4 -groupoid and a group with a special element eX. Given a,bX, we have (ab)(b(ab))=ab. Since every group has cancellation laws, we obtain b(ab)=e. By applying ( R 4 2), we have e(ab)=e, i.e., ab=e. By ( R 4 1), b=e(be)=e. This proves that |X|=1, proving the proposition. □

Proposition 5.13 Every implicative BCK-algebra is an R 4 -groupoid.

Proof If (X,,0) is an implicative BCK-algebra, then a(ba)=a and (ab)b=ab for any a,bX. It follows immediately that (X,) is an R 4 -groupoid. □

Remark The condition, implicativity, is important for a BCK-algebra to be an R 4 -groupoid.

Example 5.14 Let X:={0,1,2,3} be a set with the following table:

Then (X,,0) is a BCK-algebra, but not implicative, since 1(31)=01. Moreover, it is not a R 4 -groupoid since 32=10=(32)[2(32)].

Theorem 5.15 Every BCK-algebra (X,,0) inherited from a poset (X,) is an R 4 -groupoid.

Proof If (X,,0) is a BCK-algebra (X,,0) inherited from a poset (X,), then the operation ‘’ is defined by

xy:={ 0 if  x y , x otherwise .

Then the condition ( R 4 1) holds. In fact, given x,yX, if xy, then xy=0 and yx=y. It follows that (xy)(y(xy))=0(y0)=0=xy. If yx, then yx=0 and xy=x. It follows that (xy)(y(xy))=x(yx)=x0=x=xy. If x and y are incomparable, then xy=x and yx=y. It follows that (xy)(y(xy))=x(yx)=xy.

We claim that ( R 4 2) holds. Given x,yX, if xy, then xy=0, yx=y. It follows that (y(xy))(xy)=(y0)0=y=y0=y(xy). If yx, then yx=0, xy=x. It follows that (y(xy))(xy)=(yx)x=0x=0=yx=y(xy). If x and y are incomparable, then xy=x and yx=y. It follows that (y(xy))(xy)=(yx)x=yx=y(xy). This proves that the BCK-algebra (X,,0) inherited from a poset (X,) is an R 4 -groupoid. □

Note that the BCK-algebra (X,,0) inherited from a poset (X,) need not be an implicative BCK-algebra unless the poset (X,) is an antichain [[14], Corollary 9].

Example 5.16 Let (X,) be a left-zero semigroup, i.e., xy=x for all x,yX. Then (X,) is an R 4 -groupoid, but not a BCK-algebra.

References

  1. 1.

    Atanassov KT, Atanassova V, Shannon AG, Turner JC: New Visual Perspectives on Fibonacci Numbers. World Scientific, Singapore; 2002.

    Google Scholar 

  2. 2.

    Dunlap RA: The Golden Ratio and Fibonacci Numbers. World Scientific, Singapore; 1997.

    Google Scholar 

  3. 3.

    Kim HS, Neggers J: Fibonacci means and golden section mean. Comput. Math. Appl. 2008, 56: 228–232. 10.1016/j.camwa.2007.12.003

    MathSciNet  Article  Google Scholar 

  4. 4.

    Han JS, Kim HS, Neggers J: The Fibonacci norm of a positive integer n -observations and conjectures. Int. J. Number Theory 2010, 6: 371–385. 10.1142/S1793042110003009

    MathSciNet  Article  Google Scholar 

  5. 5.

    Han JS, Kim HS, Neggers J: Fibonacci sequences in groupoids. Adv. Differ. Equ. 2012., 2012: Article ID 19. doi:10.1186/1687–1847–2012–19

    Google Scholar 

  6. 6.

    Ma X, Zhan J, Jun YB: Some kinds of (ϵ,ϵq) -interval-valued fuzzy ideals of BCI -algebras. Inf. Sci. 2008, 178: 3738–3754. 10.1016/j.ins.2008.06.006

    MathSciNet  Article  Google Scholar 

  7. 7.

    Ma X, Zhan J, Jun YB: Some kinds of ( ϵ γ , ϵ γ q δ ) -fuzzy ideals of BCI -algebras. Comput. Math. Appl. 2011, 61: 1005–1015. 10.1016/j.camwa.2010.12.049

    MathSciNet  Article  Google Scholar 

  8. 8.

    Zhan J, Jun YB: On (ϵ,ϵq) -fuzzy ideals of BCI -algebras. Neural Comput. Appl. 2011, 20: 319–328. 10.1007/s00521-010-0376-6

    Article  Google Scholar 

  9. 9.

    Zhan J, Tan Z: m -maps of BCK -algebras. Sci. Math. Jpn. 2002, 56: 309–311.

    MathSciNet  Google Scholar 

  10. 10.

    Zhan J, Tan Z: On the kp -radical in BCI -algebras. Sci. Math. Jpn. 2002, 56: 309–311.

    MathSciNet  Google Scholar 

  11. 11.

    Allen PJ, Kim HS, Neggers J:Smarandache disjoint in BCK/d-algebras. Sci. Math. Jpn. 2005, 61: 447–449.

    MathSciNet  Google Scholar 

  12. 12.

    Neggers J, Kim HS: On d -algebras. Math. Slovaca 1999, 49: 19–26.

    MathSciNet  Google Scholar 

  13. 13.

    Meng J, Jun YB: BCK-Algebras. Kyung Moon Sa Co., Seoul; 1994.

    Google Scholar 

  14. 14.

    Kim JY, Jun YB, Kim HS: BCK -algebras inherited from the posets. Sci. Math. Jpn. 1997, 45: 119–123.

    MathSciNet  Google Scholar 

Download references

Acknowledgements

The authors are grateful for the referee’s valuable suggestions and help.

Author information

Affiliations

Authors

Corresponding author

Correspondence to Keum Sook So.

Additional information

Competing interests

The authors declare that they have no competing interests.

Authors’ contributions

All authors conceived of the study, participated in its design and coordination, drafted the manuscript, participated in the sequence alignment, and read and approved the final manuscript.

Rights and permissions

Reprints and Permissions

About this article

Cite this article

Kim, H.S., Neggers, J. & So, K.S. Generalized Fibonacci sequences in groupoids. Adv Differ Equ 2013, 26 (2013). https://doi.org/10.1186/1687-1847-2013-26

Download citation

Keywords

  • (generalized) Fibonacci sequences
  • ( L 4 , LRL 2 , R 4 )-groupoids
  • d/BCK-algebra
  • (pre-)idempotent
  • Smarandache disjoint
\